Diving into the depths of identity construction and motivation of a foreign language learner - Lazzaro-Salazar, Mariana Virginia (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
Moving away from the bilingual assumptions that have traditionally informed the study of language learners’ identity construction, this paper draws on cutting-edge SLA and sociolinguistic theories to explore the close relationship between identity and motivation in foreign language learning contexts. To this end, this paper presents some preliminary observations of a case study in progress involving a language learner who struggles to display his professional identity with the linguistic resources available to him. This, coupled with the social prestige acquired for learning a foreign language, acts as a motivating force for improving his language skills. Finally, adopting an emic perspective, the paper outlines some of the linguistic and socio-pragmatic areas the participant reports as problematic when displaying his professional self.